2014
DOI: 10.1111/jace.13045
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity in Poled Hydroxyapatite Ceramics

Abstract: Direct current electrical poling of textured hydroxyapatite (HAp) ceramics is reported here to exhibit weak ferroelectricity and pyroelectricity, but a remarkably higher (six orders of magnitude) piezoelectricity. The piezoelectric strain coefficient is an order higher than that of bone and of the same order as that of quartz crystal and uncalcified collagen in tendon. The piezoelectric charge coefficient is an order higher than bone, and three orders higher than that of tendon. Piezoelectric constants of pole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Much more significant piezoelectricity, as high as six orders of magnitude higher than that measured as shear piezoelectricity, has been obtained recently in textured hydroxyapatite ceramic that was poled under much higher electric field but at relatively lower temperature, 95 °C [11]. The piezoelectric strain coefficient, d33, is an order higher than that of bone and of the same order as that of quartz crystal and uncalcified collagen in tendon.…”
Section: Piezo-pyro-ferroelctricitymentioning
confidence: 94%
“…Much more significant piezoelectricity, as high as six orders of magnitude higher than that measured as shear piezoelectricity, has been obtained recently in textured hydroxyapatite ceramic that was poled under much higher electric field but at relatively lower temperature, 95 °C [11]. The piezoelectric strain coefficient, d33, is an order higher than that of bone and of the same order as that of quartz crystal and uncalcified collagen in tendon.…”
Section: Piezo-pyro-ferroelctricitymentioning
confidence: 94%
“…Occasionally, an interest to both electric/dielectric [304,[377][378][379][380][381][382][383][384][385][386][387][388][389][390] and piezoelectric [391,392] properties of CaPO 4 bioceramics is expressed. For example, a surface ionic conductivity of both porous and dense HA bioceramics was examined for humidity sensor applications, since the room temperature conductivity was influenced by relative humidity [378].…”
Section: Electric/dielectric and Piezoelectric Propertiesmentioning
confidence: 99%
“…Hydroxyapatite (HA) is one of the widely used synthetic material for bone graft substitutes. 7 Synthetic nanocrystalline HA has recently been demonstrated 8 to exhibit piezo, pyro and ferroelectric property. A.Gandhi et al 8 reported that a combination of optimized poling conditions and texture in HA has resulted in a longitudinal piezoelectric strain co-efficient that is one order higher than that of bone and of the same order as that of the uncalcified collagen in the tendon.…”
Section: Introductionmentioning
confidence: 99%